Carbon Disulfide (CS) Mechanisms in Formation of Atmospheric Carbon Dioxide (CO) Formation from Unconventional Shale Gas Extraction and Processing Operations and Global Climate Change - Alisa L. Rich; Jay T. Patel (SAGE Publishing, 2015)
Carbon disulfide (CS 2 ) has been historically associated with the production of rayon, cellophane, and carbon tetrachloride. This study identifies multiple mechanisms by which CS 2 contributes to the formation of CO 2 in the atmosphere. CS 2 and other associated sulfide compounds were found by this study to be present in emissions from unconventional shale gas extraction and processing (E&P) operations. The breakdown products of CS 2 ; carbonyl sulfide (COS), carbon monoxide (CO), and sulfur dioxide (SO 2 ) are indirect greenhouse gases (GHGs) that contribute to CO 2 levels in the atmosphere. The heat-trapping nature of CO 2 has been found to increase the surface temperature, resulting in regional and global climate change. The purpose of this study is to identify five mechanisms by which CS 2 and the breakdown products of CS 2 contribute to atmospheric concentrations of CO 2 . The five mechanisms of CO 2 formation are as follows: 1. Chemical Interaction of CS 2 and hydrogen sulfide (H 2 S) present in natural gas at high temperatures, resulting in CO 2 formation; 2. Combustion of CS 2 in the presence of oxygen producing SO 2 and CO 2 ; 3. Photolysis of CS 2 leading to the formation of COS, CO, and SO 2 , which are indirect contributors to CO 2 formation; 4. One-step hydrolysis of CS 2 , producing reactive intermediates and ultimately forming H 2 S and CO 2 ; 5. Two-step hydrolysis of CS 2 forming the reactive COS intermediate that reacts with an additional water molecule, ultimately forming H 2 S and CO 2 . CS 2 and COS additionally are implicated in the formation of SO 2 in the stratosphere and/or troposphere. SO 2 is an indirect contributor to CO 2 formation and is implicated in global climate change.